2010
DOI: 10.1080/17517575.2010.491871
|View full text |Cite
|
Sign up to set email alerts
|

Extending enterprise architecture modelling with business goals and requirements

Abstract: The methods for enterprise architecture (EA), such as The Open Group Architecture Framework, acknowledge the importance of requirements modelling in the development of EAs. Modelling support is needed to specify, document, communicate and reason about goals and requirements. The current modelling techniques for EA focus on the products, services, processes and applications of an enterprise. In addition, techniques may be provided to describe structured requirements lists and use cases. Little support is availa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
110
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 111 publications
(111 citation statements)
references
References 23 publications
0
110
0
1
Order By: Relevance
“…At the process level, for example, there are process and activity concepts [13]. At the strategic and operational levels of IT, it was also possible to identify a conceptual standard [1] [5]. The analysis performed in the correlated work identified, showed that information technology is relevant to organizational performance and contributes directly to business operations.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…At the process level, for example, there are process and activity concepts [13]. At the strategic and operational levels of IT, it was also possible to identify a conceptual standard [1] [5]. The analysis performed in the correlated work identified, showed that information technology is relevant to organizational performance and contributes directly to business operations.…”
Section: Related Workmentioning
confidence: 99%
“…The evaluation of the analyzed works indicated that the contributions of [2] and [5] that originated the languages BSC-P and ARMOR can be adapted to allow the closure of the gaps found in the themes associated to criteria I and II, since these works deal theorically traceability between models that are associated with criterion III. The B-SCP, also stands out as a contribution, due to the validation and verification of business requirements models, in terms of business process and strategy, which may allow an adaptation to the reality of the I criteria and II.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…ArchiMate 1.0 does not include such concepts. Nevertheless, a proposal for ArchiMate's extension in this sense has been made [9] to provide modeling support for business requirements management. This extension facilitates the identification, description, analysis and validation of requirements at business level and their realization in enterprise architecture models as described with the current ArchiMate 1.0 concepts.…”
Section: Motivation Extensionmentioning
confidence: 99%
“…A proposal for extending ArchiMate with motivation concepts has been made by Engelsman et al (2011) first. This extension is now part of the official ArchiMate 2.0 standard specification, and is described briefly in the sequel.…”
Section: Motivation Extensionmentioning
confidence: 99%